Accumulation of an endogenous tryptophan-derived metabolite in colorectal and breast cancers - Puccetti, Paolo; Platten, Michael (PLOS ONE, 2015)
Tumor immune escape mechanisms are being regarded as suitable targets for tumor therapy. Among these, tryptophan catabolism plays a central role in creating an immunosuppressive environment, leading to tolerance to potentially immunogenic tumor antigens. Tryptophan catabolism is initiated by either indoleamine 2,3-dioxygenase (IDO-1/-2) or tryptophan 2,3-dioxygenase 2 (TDO2), resulting in biostatic tryptophan starvation and l-kynurenine production, which participates in shaping the dynamic relationship of the host’s immune system with tumor cells. Current immunotherapy strategies include blockade of IDO-1/-2 or TDO2, to restore efficient antitumor responses. Patients who might benefit from this approach are currently identified based on expression analyses of IDO-1/-2 or TDO2 in tumor tissue and/or enzymatic activity assessed by kynurenine/tryptophan ratios in the serum. We developed a monoclonal antibody targeting l-kynurenine as an in situ biomarker of IDO-1/-2 or TDO2 activity. Using Tissue Micro Array technology and immunostaining, colorectal and breast cancer patients were phenotyped based on l-kynurenine production. In colorectal cancer l-kynurenine was not unequivocally associated with IDO-1 expression, suggesting that the mere expression of tryptophan catabolic enzymes is not sufficiently informative for optimal immunotherapy.